Clinical Antitumor effects of Curcumin in Prostate Cancer Environment: A Meta-Analysis - Shirdel, Ahmadreza; Zhian Zargaran, Farahnaz; Meshkat, Mojtaba; Amirabadi, Amir (Novelty in Biomedicine, 2025)
Background: Curcuma longa L. is increasingly acknowledged as a chemopreventive agent for cancer and is currently being administered to humans. Nonetheless, the limited number of clinical trials conducted for prostate cancer treatment is significant. Our objective was to conduct a meta-analysis study to evaluate curcumin’s tumor-inhibitory effects in humans. Materials and Methods: PubMed, Embase, Scopus, and Web of Science databases were searched until October 2024 to retrieve relevant articles. The RAYYAN intelligence tool for systematic reviews was incorporated for screening studies. STATA v18 software was used to conduct the meta-analysis. Egger’s test for publication bias assessment was implemented. The JBI critical appraisal tool was used to evaluate the qualities of the included studies. A plot digitizer was used to extract digital data. Results: This meta-analysis evaluated the effects of curcumin on prostate cancer. Eight studies involving 638 participants were included out of 1,523 articles. The analysis showed that curcumin significantly reduces prostate cancer incidence, with a pooled effect size of -0.91 (95% CI: [-1.68, -0.14], P = 0.02). The results indicated significant heterogeneity among studies, though a slight publication bias was noted. Conclusion: Curcumin demonstrated a favorable effect on prostate cancer treatment and exhibited inhibitory properties toward prostate tumor growth, thereby providing substantiation for additional clinical investigations. Including a limited number of studies resulted in a significant degree of heterogeneity among the included studies, which is a critical point to recognize. As a result, additional randomized controlled trials are necessary to thoroughly evaluate curcumin’s efficacy in humans.